ECTOPIC MURAL PREGNANCY - T. B. MAKUKHINA; V. V. MAKUKHINA (Кубанский научный медицинский вестник, 2017)
Aim. Systemization and analysis of published data to define terminology, risk factors, diagnostic methods and treatment strategy for ectopic mural pregnancy. Materials and methods. Keyword search of information published on electronic bibliographic databases PubMed and Cochrane Library. Limitations: English language, period till October 31, 2017 inclusive. For analysis we curated studies containing information about risk factors, diagnostic methods and criteria and treatment methods or prospective observation of ectopic mural pregnancy. The studies were divided in following categories: case report, review, clinical trial, randomized clinical investigation, systematic reviews and meta-analyses; abstracts and articles were calculated separately. Results. We found 1425 sources corresponding to the keywords. Among 1006 studies included in the review according to inclusion criteria there were 236 articles and 770 abstracts of which there were 863 case reports, 129 reviews, 5 clinical trials, 4 randomized clinical investigations, 5 systematic reviews. Ectopic mural pregnancy includes different forms with specific risk factors; in some cases pregnancy prolongation till fetus livability is possible. The main diagnostic method is ultrasound. Diagnostic terms and treatment methods are not standardized. Conclusion. Due to the rarity of this pathology and high risk of dangerous complications including fertility loss and lethal outcomes there is a need for a national audit of mural ectopic pregnancies with a database establishment for possible outcomes analysis and an individual prognosis assessment. It is necessary to develop clinical guidelines to raise the level of doctors’ awareness about the rare forms of ectopic pregnancies and improve standards of medical treatments.